Experimental investigation of the performance of a solar dryer integrated with solid desiccant coloums using water based solar collector for medicinal herb - M. Yahya; R. Hasibuan; R. Sundari; K. Sopian (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
This study is concerned with the analyses of performance on a solar dryer integrated with solid desiccant coloums using water based solar collector. The dryer consists of a solar water collector, two solid desiccant coloums, a water storage tank, two heat exchangers, an air heater, and a drying chamber. The dryer decreased the Centella asiatica L moisture content from 88.3% (wb) to 15.9% (wb) within 12 hours, with an average temperature and relative humidity of 45.4°C and 25.8%, respectively. The rate of moisture evaporation and the specific moisture evaporation rate were in the range of 0.001-1.762kg/h and 0.02-0.482 kg/kWh, with 0.594kg/h and 0.169kg/kWh in average values, respectively. The dryer efficiency was in the range of 0.62%-30.4%, with 15.4% in average value. The energy required for moisture evaporation and total energy input to the dryer were in the range of 26.9-1132.2W and 3638.0-4329.7W, with 601.8 W and 3967.4 W in average values, respectively. The efficiency of collector and the heat exchanger effectiveness were in the range of 38.1-50.5% and 65.1-79.7%, with 45.0% and 73.0% in average values, respectively. The result shows that the dryer is suitable for drying Centella asiatica L, this is due to the low temperature of drying air and high moisture evaporation rate.